2011
DOI: 10.1597/09-210
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' and Fathers' Reports of Stress in Families of Infants with and without Single-Suture Craniosynostosis

Abstract: Objective To compare relative levels of stress reported by mothers and fathers in families containing infants with and without single-suture craniosynostosis. Design Case-control study. Participants Mothers and fathers of 246 infants with recently diagnosed single-suture craniosynostosis and 253 frequency-matched control infants completed the Parenting Stress Index just prior to their infant’s cranioplastic surgery. Family demographic information and mothers’ ratings of the severity of their child’s single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 69 publications
(91 reference statements)
2
25
0
Order By: Relevance
“…The findings are consistent with a number of previous studies [2, 8, 15, 16, 28, 35-37, 42, 47, 52] which also showed that women had greater reactivity compared to Victimization and employment/finance problems were not included in the adjusted analyses due to the absence of statistically significant associations between these outcomes and gender in men across a number of life event domains of: interpersonal relationships [8,16,28,35,47]; family/home stressors [2,15,35,42,45,52] and health problems [29,35]. No statistically significant gender difference was found for victimization which is inconsistent with the literature [29,37].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The findings are consistent with a number of previous studies [2, 8, 15, 16, 28, 35-37, 42, 47, 52] which also showed that women had greater reactivity compared to Victimization and employment/finance problems were not included in the adjusted analyses due to the absence of statistically significant associations between these outcomes and gender in men across a number of life event domains of: interpersonal relationships [8,16,28,35,47]; family/home stressors [2,15,35,42,45,52] and health problems [29,35]. No statistically significant gender difference was found for victimization which is inconsistent with the literature [29,37].…”
Section: Discussionsupporting
confidence: 90%
“…First, this study employed a wide range of life event domains to examine gender differences in associations between life events and distress. In contrast, other studies have generally limited examination to specific life event domains such as: interpersonal relationship difficulties [8,16,28,47]; family and home stressors [2,42,52]; and serious health problems [45]. Comparison across domains within the same data set allows a more comprehensive examination of possible gender differences, with individuals serving as their own controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rosenberg et al reported that visibility of the condition should be considered a risk factor for increased stress in mothers of infants with single-suture craniosynostosis. 31 Similarly, Vermaes et al reported that the severity of a physical dysfunction in a child is positively associated with parenting stress. 32 Because congenital hand or foot differences are conspicuous, mothers may have a higher level of parenting stress considering the appearance of their child and, therefore, may have a tendency to seek proper treatments more actively.…”
mentioning
confidence: 98%